Mengembangkan Diseminasi Official Statistics: Peluang dan Tantangan dalam Inovasi Layanan Statistik - Tiyas Ambarsari; Triana Rachmaningsih; Hady Suryono (Seminar Nasional Official Statistics, 2021)
Statistics Indonesia (BPS) functions as the main source of official statistical data and has the responsibility to disseminate data for public use. To achieve this mission, many initiatives are undertaken to create innovations that make data easier to find, use and access effectively and efficiently. The Data Needs Survey (SKD) is one of the initiatives carried out to identify statistical data needs and the level of consumer satisfaction with BPS data and services. In this paper, we will explain the dissemination method approach through websites and data portals as a statistical service innovation to develop the dissemination of official statistics based on the IPA (Importance and Performance Analysis) and gap analysis methods. The results show that the gap analysis of statistical service attributes is -0.02 to -0.31 and the IPA analysis shows that there is an opportunity for innovation development in website services in Quadrant A which is the main priority for improvement. Keywords: official statistics, dissemination, gap analysis, importance and performance analysis